The Cultural and Literary World of Alisher Navoi in The of Studies of Evgenii Bertels - Sharifa, Usmonova (Researchparks Publishing, 2026)
This article explores the life, works, and enduring significance of the great Uzbek poet and thinker Alisher Navoi (1441–1501) as presented in Yevgeniy Bertels’ seminal monograph Navoi. While Navoi has long been celebrated as the founder of classical Uzbek literature, his role as a statesman, philosopher, and cultural reformer is equally vital. Drawing primarily on Bertels’ comprehensive study, this article examines Navoi’s biography, his literary and intellectual contributions, his cultural environment in Timurid Herat, and his intellectual companionship with contemporaries such as Jami. Through this discussion, the article highlights both the historical importance of Navoi’s works and their relevance in shaping Central Asian literary traditions.